The impact of China's urban and rural economic revitalization on the utilization of mental health inpatient services - Yan, Yu; Tu, Yongqian (Frontiers in Public Health, 2023)
Background:Rural locations have a lower preference for mental health care than urban areas. Medical and pharmacy expenses incurred as a result of serious mental illness are covered by public health insurance, according to the People's Republic of China's Mental Health Law. The study's goal was to acknowledge the disparities in the use of mental health services provided by the government health schemes among the rural and urban populations of China. This study puts light on China's ongoing healthcare reforms for mental health treatments. Furthermore, to assess the real reimbursement rates for health insurance coverage. Materials and Methods:Retrospective cohort study of patients was done that were hospitalized with mental illnesses to assess rural-urban disparities in the utilization of mental health services, and the role of health insurance. We used electronic health data from the major psychiatric institutes for 15 years (2005 to 2020) to assess the influence of health insurance systems on Chinese public preferences for mental health treatments. These psychiatric hospitals serve almost 10% of all mental health patients every year in Shandong and accept patients from all over the country. In addition, health insurance policy regulations in Shandong Province are consistent with national health insurance policy regulations. Models 1 and 2 assess disparities in the utilization of mental health treatments. Our study population was identified using patients’ primary diagnosis, as recorded in the two hospitals’ EHRs, which routinely record information on patients’ socio-demographic characteristics, clinical characteristics of the disease, cost of the treatment, and type of the health insurance plan. Results: Urban patients had longer hospital stays (p 0.0001), more hospitalizations (p = 0.006), and greater hospitalisation expenses (p = 0.001) than rural patients. Patients who had insurance had a longer hospital stay (p 0.0001), more hospitalizations (p 0.0001), and greater hospitalization costs (p 0.0001) than those who did not have insurance. Urban residents used mental health services more than rural residents. Conclusions: Rural people of China feel mental health services are an economic burden.Uniform measures are required to be taken for the development of health insurance policies for people inrural areas.